Emergent flat band electronic structure in a VSe2/Bi2Se3 heterostructure - Turgut Yilmaz (Nature Portfolio, 2021)
Dispersionless flat bands are often required to observe unusual quantum states of matter. Here, angle-resolved photoemission spectroscopy (ARPES) reveals a flat band electronic structure in a VSe2/Bi2Se3 heterostructure, and exhibits complex circular dichroism.